Bank performance and Non-interest income diversification: Evidence from Chinese commercial banks. - Yuan Zhao; Yixi Mei; Jun Wang (PLoS ONE)
This paper aims to investigate the impact of non-interest income diversification on the performance of commercial banks in China. We conduct an empirical analysis using the panel data of 159 Chinese commercial banks from 2006 to 2020. The results indicate that there is a positive relationship between the degree of non-interest income diversification and bank performance. We suggest the commercial banks to actively develop diversified non-interest business and to balance the proportion of interest and non-interest income. Furthermore, we conduct heterogeneity analysis and find remarkable differences existing among different types of commercial banks. The results show that the effect of non-interest income diversification on bank performance is more significant for the small-sized or local commercial banks whose target customers are local residents. We also take a further analysis with interaction terms and find that the positive effect of non-interest income diversification on bank performance is stronger for those with higher market competitiveness. Our findings have implications for bank managers about expanding banks' income resources through diversified business strategies and can provide experience for small or local banks seeking to advance the performance.